Frequency of use and acceptability of clinical prediction rules for pulmonary embolism among Swiss general internal medicine residents. Issue 160 (December 2017) - Faller, N.; Stalder, O.; Limacher, A.; Bassetti, S.; Beer, J.H.; Genné, D.; Battegay, E.; Hayoz, D.; Leuppi, J.; Mueller, B.; Perrier, A.; Waeber, G.; et al.
Abstract: Introduction: Whether clinical prediction rules for pulmonary embolism are accepted and used among general internal medicine residents remains uncertain. We therefore evaluated the frequency of use and acceptability of the Revised Geneva Score (RGS) and the Pulmonary Embolism Severity Index (PESI), and explored which factors were associated with rule use. Materials/methods: In an online survey among general internal medicine residents from 10 Swiss hospitals, we assessed rule acceptability using the Ottawa Acceptability of Decision Rules Instrument (OADRI) and explored the association between physician and training-related factors and rule use using mixed logistic regression models. Results: The response rate was 50.4% (433/859). Overall, 61% and 36% of the residents reported that they always or regularly use the RGS and the PESI, respectively. The mean overall OADRI score was 4.3 (scale 0–6) for the RGS and 4.1 for the PESI, indicating a good acceptability. Rule acceptability (odds ratio [OR] 6.19 per point, 95% confidence interval [CI] 3.64–10.51), prior training in emergency medicine (OR 5.14, CI 2.20–12.01), and availability of internal guidelines recommending RGS use (OR 4.25, CI 2.15–8.43) were associated with RGS use. Rule acceptability (OR 6.43 per point, CI 4.17–9.92) and rule taught at medical school (OR 2.06, CI 1.24–3.43) were associated with PESI use. Conclusions: The RGS was more frequently used than the PESI. Both rules were considered acceptable. Rule acceptability, prior training in emergency medicine, availability of internal guidelines, and rule taught at medical school were associated with rule use and represent potential targets for quality improvement interventions. Highlights: The use of the Revised Geneva Score (RGS)/Pulmonary Embolism Severity Index (PESI) is unknown. We conducted an online survey among Swiss general internal medicine residents. The RGS was more often used than the PESI (61% vs. 36%). Both the RGS and the PESI were considered acceptable. Educational factors were related with rule use and are targets for interventions.